Stadsbruk : i vilken mån kan Malmö kompensera för den åkermark som förstörs - Borg Nilsson, Izabelle; Funck, Madeleine (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2022)
Title: Urban farming- To what degree can Malmö compensate for destroying arable land Seminar date: 2022-03-xx Course: EX0845: Bachelor thesis in Landscape architecture, Undergraduate Level, 15 Credits Advisor: Love Silow Authors: Izabelle Borg Nilsson, Madeleine Funck Keywords: Urban farming, sustainability, urbanization, agriculture Purpose: The purpose of this thesis is that through qualitative research contribute the reader with information about how and if cities can compensate for the arable land it uses for expanding and urbanization and if it can be done through urban farming. Furthermore, we intend to investigate if and what urban farming can offer a city. Methodology: The thesis has a qualitative approach where the empirical findings have been collected through three semi-structured in-depth interviews. Theoretical perspectives: The thesis is mainly based on theory from several research papers about self sustainable cities. Conclusions: In this thesis after collecting information both through literature and interviews we have come to the conclusion that it is difficult for cities to compensate for the destruction of arable land. Urban farming cannot be compared to arable land, but brings many positive aspects to the city anyway. Cities can compensate the destruction of arable land to some degree in various ways, but only to a small extent. Urban farming can not in its current form produce enough to make a city self-sustained on vegetables but it can cover if one is optimistic around 20% of its consumption and it could have covered it fully if the cities made major investments and restructures. But after discussing it with city officials it seems to be an unlikely scenario since other areas of interest would be given priority.